Community assembly following disturbance in batch anaerobic digesters displays highly reproducible secondary succession and a shifting stochastic-deterministic balance - Guerrero-Toledo, Flor de María; Espinosa-Solares, Teodoro; Hernández-Eugenio, Guadalupe; Huber, David H. (Frontiers in Microbiomes, 2026)
The great diversity of anaerobic digestion (AD) microbiomes indicates high redundancy and flexibility in the assembly of the community. Moreover, AD microbiomes are frequently subjected to disturbances during start-up and operation that require (re)assembly. We tested the reproducibility of secondary succession and AD community assembly mechanisms using a pre-assembled microbiome that was subjected to intense disturbances. Microbiome diversity and functions were followed in replicate mesophilic batch digesters initiated with multiple stressors, including high feed-to-inoculum ratio and many foreign species. Three 10 L batch digesters were derived from a single long-term CSTR digester pre-adapted to poultry litter feedstock and operated in parallel. Physicochemical parameters (methane, acetate, propionate, butyrate, pH, N-NH3, COD) were measured. Metagenome samples were used to assess diversity and functions. Three performance phases were found along the successional gradient: (1) methane inhibition, (2) high methane production, and (3) low methane plateau. The inventory of species (>1600) remained nearly the same, however the relative abundance of species, families, and functions changed during each successional stage. Syntrophic bacteria peaked in abundance during the mid-succession, high methane stage. Succession of overall KEGG functions was highly similar although species and carbohydrate functions diverged during late succession, suggesting diversity of niche partitioning during degradation of recalcitrant organic matter. We estimated the relative contributions of stochastic and deterministic processes and found a shift in the balance during succession. Early succession was not dominated by either dispersal or selection while late succession was dominated by variable selection. In conclusion, methane production recovered following severe (non-lethal) disturbance in a pre-adapted digester microbiome through a reproducible community assembly pathway that shifted toward deterministic, variable selection over time.